SCALE OF INJURIES RISK DUE TO XEROSIS IN HOSPITALIZED ELDERLY PEOPLE: DEVELOPMENT AND EVIDENCE VALIDITY (Estima – Brazilian Journal of Enterostomal Therapy, 2024)
Objective: To describe the construction process and validation evidence of the risk assessment scale for the development of lesions associated with cutaneous xerosis in hospitalized elderly people. Method: Methodological study based on Pasquali’s psychometric validation through theoretical, empirical, and analytical analysis. Operationalization occurred in three stages: scope review, scale construction, and content validation by expertises. Results: The instrument is structured in 14 items, with an overall score ranging between 15 (low risk) and 53 (high risk), and presented a content validity coefficient of 0.926 based on the aspects theoretical relevance, theoretical dimension, clarity of language, and practical relevance. It also presented a general Cronbach’s alpha of 0.815, as well as a McDonald’s omega of 0.942, which reveals excellent internal consistency. Conclusion: The instrument showed evidence of validity and could contribute to nurses’ practice when integrating the skin care process for elderly people.